Deciphering the maize gene ZmGF14–3: implications for plant height based on co-expression networks - Wang, Hengsheng; Wei, Bo; Qi, Lulu; Chen, Yansong; Chen, Kelong; Liu, Dong; Su, Xu; Zhang, Yan; Li, Lingling (Frontiers in Plant Science, 2024)
The GF14 gene family, ubiquitous in all eukaryotic organisms, plays a pivotal role in a series of biological processes, intricately influencing the regulation of plant growth and development. The evolutionary analysis showed that the GF14 family was conserved, however, there was limited evidence linking GF14s to plant height. In our investigations, we discovered a co-expression relationship between ZmGF14s and functionally characterized genes linked to plant height. Moreover, a significant correlation was observed between the expression levels of ZmGF14s and genes associated with plant height throughout different developmental stages of maize. In the co-expression network, we identified ZmGF14-3, a gene expression exhibiting a positive correlation with plant height in three maize varieties, we postulated that this gene could be intimately linked to plant height development. Subsequently, we cloned ZmGF14-3 from the maize B73 inbred line and overexpressed it in Arabidopsis, resulting in markedly dwarfed transgenic phenotypes. Subcellular localization results indicated that ZmGF14-3 predominantly exhibited a punctate pattern of localization in protoplasts, primarily concentrating in the cytoplasm. Meanwhile, tissue expression pattern results showed elevated expression of ZmGF14-3 in the stem. Measurements of endogenous * Corresponding